Complexin Stabilizes Newly Primed Synaptic Vesicles and Prevents Their Premature Fusion at the Mouse Calyx of Held Synapse - Chang, Shuwen; Reim, Kerstin; Pedersen, Meike; Neher, Erwin; Brose, Nils; Taschenberger, Holger (The Journal of neuroscience, 2015)
Complexins (Cplxs) are small synaptic proteins that cooperate with SNARE-complexes in the control of synaptic vesicle (SV) fusion. Studies involving genetic mutation, knock-down, or knock-out indicated two key functions of Cplx that are not mutually exclusive but cannot easily be reconciled, one in facilitating SV fusion, and one in “clamping” SVs to prevent premature fusion. Most studies on the role of Cplxs in mammalian synapse function have relied on cultured neurons, heterologous expression systems, or membrane fusion assays in vitro , whereas little is known about the function of Cplxs in native synapses. We therefore studied consequences of genetic ablation of Cplx1 in the mouse calyx of Held synapse, and discovered a developmentally exacerbating phenotype of reduced spontaneous and evoked transmission but excessive asynchronous release after stimulation, compatible with combined facilitating and clamping functions of Cplx1. Because action potential waveforms, Ca 2+ influx, readily releasable SV pool size, and quantal size were unaltered, the reduced synaptic strength in the absence of Cplx1 is most likely a consequence of a decreased release probability, which is caused, in part, by less tight coupling between Ca 2+ channels and docked SV. We found further that the excessive asynchronous release in Cplx1-deficient calyces triggered aberrant action potentials in their target neurons, and slowed-down the recovery of EPSCs after depleting stimuli. The augmented asynchronous release had a delayed onset and lasted hundreds of milliseconds, indicating that it predominantly represents fusion of newly recruited SVs, which remain unstable and prone to premature fusion in the absence of Cplx1.